Integrated production and distribution scheduling with a perishable product - Devapriya, Priyantha; Ferrell, William; Geismar, Neil (European journal of operational research, 2017)
•Mathematical programming formulation solvable for small problems.•Route first, cluster second approach using makespan compression.•Bounds on routes and cost developed.•Heuristics used for realistic sized problems. This research focuses on the practical problem of a perishable product that must be produced and distributed before it becomes unusable but at minimum cost. The problem has some features of the integrated production and distribution scheduling problem in that we seek to determine the fleet size and the trucks’ routes subject to a planning horizon constraint. In particular, this research differs because the product has a limited lifetime, the total demand must be satisfied within a planning horizon, multiple trucks can be used, and the production schedule and the distribution sequence are considered. A mixed integer programming model is formulated to solve the problem and, then, heuristics based on evolutionary algorithms are provided to resolve the models.